Respon Masyarakat terhadap Program Rumah Layak Huni di Kota Dumai - Andrizayani, Putri; Hidir, Achmad; Asriwandari, Hesti (CV. Rayyan Dwi Bharata, 2025)
This study examines the community's response to the construction of decent houses in Dumai City. The author attempts to describe and analyze the community's response to the Construction of a Livable House Program in Dumai City in a factual, accurate, and systematic manner. The author uses the survey method, which, according to Masri Singarimbun in Iskandar, is